Healing of the nasal septal mucosa in an experimental rabbit model of mucosal injury - Kyu Young Choi (KeAi Communications Co., Ltd., 2017)
Objective: The aim of this study was to investigate the regeneration process of the nasal mucosa after a surgically created mucosal defect in the rabbit nasal septum, and to evaluate the effects of different interventions. Methods: A 7 mm-diameter circular mucosal defect was made in the septum of forty New Zealand white rabbits. The rabbits were divided into four groups (ten rabbits in each group) according to the type of intervention; no treatment (control), silastic sheet (SS), hyaluronic acid (HA), and silastic sheet and hyaluronic acid (SS + HA) group. The diameter of the defect, mucosal thickness, epithelial thickness, and ciliated cell count were evaluated every week for five weeks. Results: The average diameter of the defect in the control group were 5.1, 3.65, 1.2, 0.75, and 0.05 mm at postoperative 1, 2, 3, 4, and 5 weeks. In the SS group, the diameter decreased to 4.35, 2.1, 0.35, 0.15, and 0 mm at postoperative 1, 2, 3, 4, and 5 weeks, respectively, in which the mean diameter of the postoperative week 2 was significantly smaller compared to control (3.65 mm vs. 2.1 mm, P = 0.039). For the HA group and SS + HA group, the diameter of the defect did not show a significant difference from the control group during the five weeks. The mucosal thickness, epithelial thickness, and ciliated cell count of the regenerated mucosa were not significantly different among the groups. Conclusion: The regeneration process of the nasal septal mucosa was identified using a novel rabbit model. Mucosal regeneration can be accelerated by applying silastic sheets. Keywords: Nasal septum, Nasal mucosa, Mucous membrane, Hyaluronic acid, Rabbits